2015
DOI: 10.1614/wt-d-14-00142.1
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Decreases Atrazine and Pendimethalin Preemergence Herbicidal Activity

Abstract: Biochar and vinasse are by-products of biofuel production that can be used as soil amendments. However, their addition to the soil might affect PRE herbicide activity. Although studies have shown that biochar has a high herbicide adsorption capacity, there is little information available about biochar effect on weed control especially under field conditions. Therefore, the objective of this study was to determine the influence of biochar and vinasse application on atrazine and pendimethalin availability and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…Pendimethalin is a soil-applied dinitroaniline herbicide used for the control of some broadleaf and grass weeds by inhibiting mitosis. A study from the USA suggested that the use of biochar as a soil amendment could decrease pendimethalin efficacy by adsorbing a significant amount of the herbicide [35]. In another study similar to our study, pendimethalin application (1 and 2 kg ai/ha) in the presence of rice residue cover resulted in lower control of Cyperus iria L. than in the absence of residue 15 .…”
Section: Gr Gs 0 T/ha 3 T/ha 6 T/ha 0 T/ha 3 T/ha 6 T/hasupporting
confidence: 78%
“…Pendimethalin is a soil-applied dinitroaniline herbicide used for the control of some broadleaf and grass weeds by inhibiting mitosis. A study from the USA suggested that the use of biochar as a soil amendment could decrease pendimethalin efficacy by adsorbing a significant amount of the herbicide [35]. In another study similar to our study, pendimethalin application (1 and 2 kg ai/ha) in the presence of rice residue cover resulted in lower control of Cyperus iria L. than in the absence of residue 15 .…”
Section: Gr Gs 0 T/ha 3 T/ha 6 T/ha 0 T/ha 3 T/ha 6 T/hasupporting
confidence: 78%
“…[13,30,49] Other studies have shown higher sorption of neutral herbicides (treflan and pendimethalin). [32,51] Acidic herbicides, like 2,4-D, are less sorbed to soil when compared with slightly positively charged herbicides like atrazine, but sorption also is influenced by soil organic matter content and pH. [52] Kearns et al [53] reported that 2,4-D sorption to biochar (feedstocks of bamboo, pine, or corn cobs) depended on initial biochar production temperature, with greater sorption to biochars produced at higher temperatures or undergoing longer pyrolysis times.…”
Section: Discussionmentioning
confidence: 99%
“…Our germination assay results also are similar to previous studies that reported reduced herbicide uptake or weed efficacy when soils were amended with biochar. [31,32,51] For example, Nag et al [32] reported that straw biochar applied at 0.5 or 1% decreased bioavailability of atrazine and trifluralin in calcarosol and ferrosol soils types. Soni et al [51] reported a 75% reduction in weed control in the field studies with atrazine applied preemergence to soils amended with 0.5 kg m ¡2 biochar.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that atrazine was irreversible sorbed by biochar and moderately sorbed by tire chips. Biochar amendments to soils reduced weed control by atrazine up to 75% [46], suggesting that biochar is an effective sorbent for atrazine when added to the soil. The low desorption from limestone, and perhaps steel slag, may have been due to the low overall amount of atrazine sorbed by these materials.…”
Section: Desorption Stepmentioning
confidence: 99%